Analysis of intention and influencing factors on mobile information follow-up service in HIV/AIDS in a city in China - Li, Chuancang; Wang, Pengli; Zhang, Mengge; Qu, Mengbing; Cai, Qian; Meng, Jingjing; Fan, Haohao; Sun, Liang (Frontiers in Public Health, 2022)
Abstract Objective: To evaluate the willingness of Henan province’s HIV/AIDS to accept mobile information follow-up, find the key factors that affect behavioral willingness, explore its internal mechanism, and provide a theoretical basis for the further promotion of mobile follow-up work. Method: This study used the Technology Acceptance Model (TAM) as the main theoretical basis, adopted a stratified random sampling method, investigated the HIV/AIDS in the six area of Sanmenxia City. The research adopted on-site questionnaire survey method. Confirmatory factor analysis was used for structural validity, and Cronbach’s coefficient was used for reliability. Data analysis mainly uses SPSS23.0 and AMOS23.0 software. Result: The acceptance rate of HIV/AIDS mobile follow-up service was 68.53%. Product factors, subjective norms, perceived usefulness, perceived ease of use, and perceived innovation had an impact on HIV/AIDS behavioral intention. The model fitting was considered acceptable (RMSEA=0.074, GFI=0.905, NIF=0.941, TLI=0.593). Conclusion: Product factors and subjective norms have important influence on behavior intention of the HIV/AIDS who accept mobile health. Perceived usefulness was an important factor that effect on behavior intention. More convenient, safe, fast and practical products is the key to the successful development of mobile follow-up services. Keywords: Mobile follow-up service, Technology acceptance model, AIDS, Willingness to behave, Structural equation model